Bibliometric analysis of acupuncture and moxibustion treatment for mild cognitive impairment - Yang, Wei; Liu, Xingfang; Zhang, Xinyue; Li, Cong; Li, Zhenghong; Li, Yiming; Li, Mingquan (Frontiers in Neuroscience, 2023)
Objective: This study aims to analyze the current research status of acupuncture in the treatment of mild cognitive impairment (MCI) using bibliometric methods, explore current research hotspots, and predict future research trends. Methods: Literature on acupuncture for MCI in China National Knowledge Infrastructure (CNKI) and Web of Science (WOS) databases were searched from their inception to December 31, 2022. Articles were then filtered using inclusion and exclusion criteria and imported into VOSviewer 1.6.11 and CiteSpace 6.1.6msi software for descriptive analysis of publication numbers, network analysis of author/institution collaborations, and cluster analysis of keywords, as well as analysis of keyword emergence and linear relationships with time. Results: The Chinese and English databases included 243 and 565 relevant articles, respectively. The overall volume of Chinese and English literature was stable, with the annual volume generally increasing. In terms of countries, institutions, and authors, China had the highest number of English-language publications; however, the number of joint publications among institutions/authors was low. Research institutions were independent and dispersed, with no collaborative teams formed around a single institution/author. The hotspots in Chinese literature were "needling, acupuncture and moxibustion, electric acupuncture， acupuncture therapy, stroke, dementia, Cognitive trainin" and other clinical research directions. The hotspots in English literature were "acupuncture, electro-acupuncture, Alzheimer's disease, dementia, cognitive impairment, memory, vascular dementia, mild cognitive impairment, stroke, hippocampus, injury," and other mechanisms of action. Conclusion: The popularity of acupuncture for MCI is increasing year by year. Acupuncture for MCI, along with cognitive training, can help improve cognitive function. "Inflammation" is the frontier of acupuncture for MCI research. In the future, strengthening effective communication and cooperation among institutions, especially international cooperation, is essential for conducting high-quality research on acupuncture for MCI. This will help obtain high-level evidence and improve the output and translation of research results.